Cervical lymphadenopathy; toxoplasmosis in the course of Hodgkin’s disease – case report and review of literature - Gutkowski, Krzysztof; Lubas, Wojciech; Bury, Andrzej; Gutkowska, Dorota; Pluta, Andrzej (Przewodnik Lekarza/Guide for GPs, 2005)
In most cases the process of reaching the diagnosis of the patient with cervical lyphadenopathy is not so difficult. Preliminary diagnosis based on detailed anamnesis and accurate physical examination may turn out, that is agreed with final diagnosis. Although there are in clinical practice cases of two or more coexisted diseases, which demand special diagnostic procedures. Despite of the fact, that clinical course of toxoplasmosis in immunocompetent host is in most cases a self-limited process, very severe complications like pneumonitis with acute respiratory distress syndrome, myocarditis, pericarditis, polymyositis, hepatitis, or encephalitis have been reported. Therefore, proper diagnosis and fast treatment order in patients with coexisted neoplastic process and toxoplasmosis may exert significant influence on course of all chemo and/or radiotherapy process, reduce severe organ complications as well as significantly improve prognosis as to patients life. We present a case report of 16 years old female patient with cervical lymphadenopathy in the course of de novo diagnosed Hodgkin’s disease with coexisted infection of protozoon Toxoplasma gondi .